2021
DOI: 10.1186/s12943-020-01292-5
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling tumour microenvironment heterogeneity in nasopharyngeal carcinoma identifies biologically distinct immune subtypes predicting prognosis and immunotherapy responses

Abstract: Currently, there is no strong evidence of the well-established biomarkers for immune checkpoint inhibitors (ICIs) in nasopharyngeal carcinoma (NPC). Here, we aimed to reveal the heterogeneity of tumour microenvironment (TME) through virtual microdissection of gene expression profiles. An immune-enriched subtype was identified in 38% (43/113) of patients, which was characterized by significant enrichment of immune cells or immune responses. The remaining patients were therefore classified as a non-Immune Subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 14 publications
1
42
0
2
Order By: Relevance
“…Approximately 70% of patients with NPC are diagnosed at an advanced stage and are more prone to therapy failure due to radioresistance [ 2 ]. NPC is characterized by Epstein–Barr virus (EBV) infection and substantial lymphocyte infiltration [ 3 ], which consists of the immune microenvironment, indicating the importance of EBV and the tumor microenvironment in NPC pathogenesis. EBV infection is considered the most important etiological factor of NPC [ 4 ] and is reported to change the tumor microenvironment to benefit itself, particularly immune evasion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of patients with NPC are diagnosed at an advanced stage and are more prone to therapy failure due to radioresistance [ 2 ]. NPC is characterized by Epstein–Barr virus (EBV) infection and substantial lymphocyte infiltration [ 3 ], which consists of the immune microenvironment, indicating the importance of EBV and the tumor microenvironment in NPC pathogenesis. EBV infection is considered the most important etiological factor of NPC [ 4 ] and is reported to change the tumor microenvironment to benefit itself, particularly immune evasion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk transcriptomic and recently single-cell RNA sequencing (scRNA-seq) also revealed different cell populations and subtypes of TIME in NPC-broadly categorised into inflamed, hot, and immune excluded. A few studies have separately identified subtypes of NPC according to immune and nonimmune gene signatures, observing the immune gene signature-rich subtypes correlating with better survival outcomes (108,148). Chen et al described an immuneenriched stroma in 38% (43/113) of patients, characterised by significant enrichment of immune response signatures.…”
Section: Characterisation Of Time Through Transcriptomic Datamentioning
confidence: 99%
“…Recent work has detected differences in TME between various types of NPC. Certain subsets of NPC have an immune-rich TME, comprising of high concentrations of host immune cells (T-cells, B-cells, macrophages) as well as increased expression of checkpoint inhibitor proteins such as programmed death ligand 1 (PD-L1) and transforming growth factor (TGF)-beta [ 24 , 25 , 26 ] ( Figure 1 ). It is hypothesized that these immune-rich NPCs may be associated with more favorable outcomes and are more readily targeted by new therapies such as immunotherapy.…”
Section: Induction Therapymentioning
confidence: 99%
“…It is hypothesized that these immune-rich NPCs may be associated with more favorable outcomes and are more readily targeted by new therapies such as immunotherapy. The reader is referred to the excellent review that was recently published on the topic and provides a comprehensive review of the complexity of the TME within NPC [ 24 ].…”
Section: Induction Therapymentioning
confidence: 99%